The feasibility of recruiting and retaining men who have sex with men and transgender women in a multinational prospective HIV prevention research cohort study in sub‐Saharan Africa (HPTN 075). (1st October 2020) - Sandfort, Theodorus GM; L Hamilton, Erica; Marais, Anita; Guo, Xu; Sugarman, Jeremy; Chen, Ying Q; Cummings, Vanessa; Dadabhai, Sufia; Dominguez, Karen; Panchia, Ravindre; Schnabel, David; Zulu, Fatima; et al.
Abstract: Introduction: Men who have sex with men (MSM) and transgender women (TGW) in sub‐Saharan Africa (SSA) are profoundly affected by HIV with high HIV prevalence and incidence. This population also faces strong social stigma and legal barriers, potentially impeding participation in research. To date, few multi‐country longitudinal HIV research studies with MSM/TGW have been conducted in SSA. Primary objective of the HIV Prevention Trials Network (HPTN) 075 study was to assess feasibility of recruiting and retaining a multinational prospective cohort of MSM/TGW in SSA for HIV prevention research. Methods: HPTN 075, conducted from 2015 to 2017, was designed to enroll 400 MSM/TGW at four sites in SSA (100 per site: Kisumu, Kenya; Blantyre, Malawi; Cape Town, South Africa; and Soweto, South Africa). The number of HIV‐positive persons was capped at 20 per site; HIV‐positive persons already in care were excluded from participation. The one‐year study included five biobehavioural assessments. Community‐based input and risk mitigation protocols were included in study design and conduct. Results: Of 624 persons screened, 401 were enrolled. One in five participants was classified as transgender. Main reasons for ineligibility included: (a) being HIV positive after the cap was reached (29.6%); (b) not reporting anal intercourse with a man in the preceding three months (20.6%); and (c) being HIV positive and already in care (17.5%). Five (1.2%) participants died during the study (unrelated to study participation). 92.9% of the eligible participants (368/396) completed the final study visit and 86.1% participated in all visits. The main, overlapping reasons for early termination included being (a) unable to adhere to the visit schedule, predominantly because of relocation (46.4%), and (b) unable to contact the participant (32.1%). Participants reported strong motivation to participate and few participation barriers. Four participants reported social harms (loss of confidentiality and sexual harassment by study staff) that were successfully addressed. Conclusions: HPTN 075 successfully enrolled a multinational sample of MSM/TGW in SSA in a prospective HIV prevention research study with a high retention rate and few documented social harms. This supports the feasibility of conducting large‐scale research trials in this population to address its urgent, unmet HIV prevention needs.